The Service Program of “You May Not Stop From School” as a Way of the Fulfillment of Educational Rights For Street Children and Dropouts in Palembang - Ahmad Zulinto; Muhammad Kristiawan; Rambat Nur Sasongko (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
Based on statistical data from the Ministry of Education and Culture in 2018, the dropout rate in South Sumatra Province was very high. Especially for the Palembang City area, there were about 17% of the cases of children dropping out of school in South Sumatra until 2018. The large number of children who have dropped out of school and who were not in school cause exploited children to be still often found on the streets, joining their parents to earn a living and even vulnerable to being involved in various juvenile delinquency and other criminal acts. Based on this fact, the Palembang City Government (Pemkot) in 2019, through the Palembang City Education Office, then developed a program to eradicate school dropouts and street children called the "The Service Program Of You May Not Stop From School" (Poltabes). This program is followed up with education at a distance school (Filial) for street children and school dropouts in Palembang Learning Activity Center. The method used was qualitative research. The research was conducted at a filial school for street children and dropouts in Palembang city. Data collection in the study was carried out through observation, interviews, and documentation. The subjects of this study consisted of one tutor each, a companion teacher, a party from the Education Office, and students. The study found that the fulfillment of the right to education for street children and dropouts through the Filial school program at Palembang Learning Activity Center has been going well. Until the end of the 2020/2021 academic year, the implementation of this filial school program has had an impact, including: 1) 7 elementary school students, 42 junior high school students, and 44 high school students, with a total of 93 students have completed formal education; 2) street children or dropouts who attend filial school education show a change in behavior and actions in a positive direction, both in attitude and appearance; 3) a decrease in the dropout rate in the city of Palembang, which was initially 1,278 cases reduced to 491 cases; 4) support the increase in the average length of schooling which was initially 10.37% to 10.52%; 5) support the increase in the human development index from 77.89% to 78.44%; 6) This Poltabes innovation is in line with and contributes to the achievement of The Sustainable Development Goals (SDGs) in the education sector.